2016
DOI: 10.17795/jhealthscope-33065
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Atrazine Degradation in the Aqueous Phase Using Titanium Catalyst Doped With Iron (Fe+3-TiO2) Processes

Abstract: Background: Atrazine is used extensively in many parts of the world for controlling a variety of weeds, primarily in the production of corn. Its widespread use in water has caused environmental concern because of its frequent detection in aquatic systems where this herbicide has been spilled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The results of a study focusing on evaluating the feasibility of using a titanium catalyst doped with iron (Fe +3 -TiO2) to remove atrazine shows 41.72% rate of atrazine removal. It can be concluded that the Fe +3 -TiO is an appropriate method for reducing atrazine in polluted water resources [31]. Bacteria capable of degrading atrazine were isolated from the lotic water using an enrichment technique.…”
Section: Hydroxyatrazinementioning
confidence: 99%
“…The results of a study focusing on evaluating the feasibility of using a titanium catalyst doped with iron (Fe +3 -TiO2) to remove atrazine shows 41.72% rate of atrazine removal. It can be concluded that the Fe +3 -TiO is an appropriate method for reducing atrazine in polluted water resources [31]. Bacteria capable of degrading atrazine were isolated from the lotic water using an enrichment technique.…”
Section: Hydroxyatrazinementioning
confidence: 99%
“… 10 11 12 Titanium dioxide (with three crystalline phases: anatase, rutile and brookite), a white powder that has a photocatalytic and super-hydrophilic, is used in water and wastewater treatment, air pollution and buildings. 12 13 Features such as low price, availability, chemical stability and lack of toxicity make the titanium dioxide as the most appropriate photocatalyst. 14 Photocatalytic oxidation by having advantages such as an activity at ambient temperature and low pressure, low cost and low power consumption in comparison with other methods, has introduced as one of the promising alternatives for treating a wide range of volatile organic compounds in the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum allowed concentration of atrazine in drinking water in the USA is 3 ppb, and, suitable methods for its detoxification and removal from water are needed. Several materials and methods have been suggested for the removal of atrazine 4 , 5 . Reported studies focus on reverse osmosis (RO) 6 , nanofiltration (NF) 7 , physicochemical methods such as extraction and adsorption 8 , and degradation based on visible or ultraviolet radiation, heat, microwave and ultrasound 9 14 .…”
Section: Introductionmentioning
confidence: 99%